Light-driven Regeneration of Cone Visual Pigments through a Mechanism Involving RGR opsin in Müller glial cells - Morshedian, Ala (Neuron, 2019)
While rods in the mammalian retina regenerate rhodopsin through a well-characterized pathway in cells of the retinal pigment epithelium (RPE), cone visual pigments are thought to regenerate in part through an additional pathway in Müller cells of the neural retina. The proteins comprising this intrinsic retinal visual cycle are unknown. Here, we show that RGR opsin and retinol dehydrogenase-10 (Rdh10) convert all-trans-retinol to 11-cis-retinol during exposure to visible light. Isolated retinas from Rgr+/+ and Rgr−/− mice were exposed to continuous light, and cone photoresponses were recorded. Cones in Rgr−/− retinas lost sensitivity at a faster rate than cones in Rgr+/+ retinas. A similar effect was seen in Rgr+/+ retinas following treatment with the glial-cell toxin, α-aminoadipic acid. These results show that RGR opsin is a critical component of the Müller-cell visual cycle, and that regeneration of cone visual pigment can be driven by light.